2020
DOI: 10.12688/hrbopenres.13161.1
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of face masks worn in community settings at reducing the transmission of SARS-CoV-2: A rapid review

Abstract: Background: The use of face masks is part of a suite of infection prevention and control measures intended to limit the transmission of respiratory viral diseases. The use of face masks by the general public has been subject to ongoing debate, with limited direct evidence on the effectiveness of face masks in the community during the COVID-19 pandemic. The aim of this review was to synthesise direct evidence on the effectiveness of wearing face masks at reducing the transmission of SARS-CoV-2 in community sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…27 Another unpublished metaanalysis on face masks in community settings suggested that face masks significantly reduce the risk of SARS-CoV-2 infection. 28 The WHO started recommending wearing masks as part of a comprehensive approach to reducing the spread of SARS-CoV-2 in June 2020. 29 This is consistent with the recommendations made by the Chinese health department at the beginning of the epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…27 Another unpublished metaanalysis on face masks in community settings suggested that face masks significantly reduce the risk of SARS-CoV-2 infection. 28 The WHO started recommending wearing masks as part of a comprehensive approach to reducing the spread of SARS-CoV-2 in June 2020. 29 This is consistent with the recommendations made by the Chinese health department at the beginning of the epidemic.…”
Section: Discussionmentioning
confidence: 99%